Exploring Factors Affecting Property Companies' Value on the Indonesian Stock Exchange - Bella, Shinta; Apriyanti, Nike; Sriwijayanti, Hari (Equator Journal of Management and Entrepreneurship (EJME), 2024)
This research explores the influence of investment decisions, dividend policies, interest rates, and profitability on the value of property and real estate companies listed on the Indonesia Stock Exchange. The study employs quantitative research methods, utilizing partial and simultaneous statistical tests to analyze the impact of these variables. The results indicate that investment decisions and profitability significantly and positively affect company value. However, dividend policies and interest rates do not exhibit a significant impact individually. Intriguingly, when considered collectively, these variables demonstrate a significant positive influence on company value. The adjusted R square of 84.5% suggests that a substantial portion of the variability in Price Book Value can be explained by these factors. Recommendations include encouraging companies to make well-informed investment decisions to enhance profitability and overall performance. Furthermore, future research should consider expanding sample sizes and incorporating additional variables for a more comprehensive analysis.